Project-based learning online training to develop students' Islamic character for English teachers at Muhammadiyah Elementary Schools in Yogyakarta - Soviyah Soviyah; Nur Fatimah (Community Empowerment, 2022)
During the Covid-19 pandemic, teachers, including Muhammadiyah schools, encountered difficulties in terms of methods in relation to online learning. One of suitable learning model is project-based learning as it able to help students develop various positive characters, including Islamic characters. The purpose of the community service is to provide project-based online learning training for English teachers at Muhammadiyah Elementary Schools in Yogyakarta City to develop the Islamic character of students during the Covid-19 pandemic. The method is carried out through three main stages: pre-activity, main activities, and post-activity. The result is that the English teachers of Muhammadiyah Elementary School has knowledge about project-based online learning to develop the Islamic character of students during the Covid-19 pandemic. Based on the responses, it showed that the participants enthusiastically welcomed the program and hoped that it could be continued.